Legal Problems in Determining Factual Actions as Dispute Object of the State Administrative Court in Indonesia - Fadillah, Nor; Hariyanto, Hariyanto; Mourtadhoi, Abdallah (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2023)
This study’s aim is to analyze how the concept development of State Administrative Decision (KTUN) in Indonesia. It is also to analyze the legal problems of determining factual actions as the dispute object in the Administrative Court because, after the promulgation of Law Number 30 of 2014 concerning Government Administration, there are some legal effects, especially after the emergence of factual action term as renewal. This study is normative research on the rules or the Law itself and the principle of positive Law by making legal materials the object of study. The approach used in the study is the approach of legislation and conceptual approach. The research data needed in this study is through the method of literature or documents and analyzed in a descriptive-qualitative way. The results showed that the KTUN before the Law Number 30 of 2014 is a written determination issued by a state administrative body or official containing administrative legal acts based on applicable laws and regulations, which are concrete, individual and final, giving rise to legal consequences for a person or civil legal entity. While the KTUN after the renewal is a written determination that includes factual actions, decisions of bodies and/or state administration officials in the executive, legislative, judicial, and other state administrations, based on the provisions of legislation and the General Principles of Good Government (AUPB), and final in a broader sense give decisions could have the potential to cause legal consequences, and/or could apply to citizens. The renewal is to cause problems such as chaos from the meaning of terminology, for example, the use of the term decision and or action. In addition, there is no specific explanation, so it is feared that legal norms are ambiguous, especially for judges in examining cases related to factual actions.